NiFe2O4 nanoparticles: an efficient and reusable catalyst for the selective oxidation of benzyl alcohol to benzaldehyde under mild conditions. Issue 12 (6th November 2020) - Iraqui, Saddam; Kashyap, Siddhartha Shankar; Rashid, Md. Harunar
Abstract : NiFe2 O4 nanoparticles of well-controlled sizes have been synthesized for use as a catalyst in the selective oxidation of benzyl alcohol. Abstract : Benzaldehyde is one of the most important and versatile organic chemicals for industrial applications. This study explores a milder approach for the fabrication of NiFe2 O4 nanoparticles (NPs) for use as a catalyst in the selective oxidation of benzyl alcohol to benzaldehyde. A co-precipitation method coupled with hydrothermal aging has been adopted to synthesize NiFe2 O4 NPs in the absence of any additive. Different techniques such as electron microscopy, diffractometry, and photoelectron spectroscopy have been used to characterize the products. The results showed that the synthesized NiFe2 O4 NPs are spherical, pure, and highly crystalline with sizes below 12 nm possessing superparamagnetic behaviour. The catalytic activity of the synthesized NiFe2 O4 NPs has been assessed in the selective oxidation of benzyl alcohol under ambient reaction conditions. A conversion of 85% benzyl alcohol with 100% selectivity has been attained with t -butyl hydroperoxide at 60 °C in 3 h. With the optimized reaction conditions, the generality of the newly developed protocol has been expanded to a wide array of substituted benzyl alcohols with good performance. The NiFe2 O4 nanocatalysts are magnetically separable and are reusable up to five cycles without loss of catalytic activity.